The Pursuit of Scholarship: Why We Should Care About Resident Research. (15th November 2017) - Bechtold, Joan E.; Williams, Benjamin R.; Weinstein, Stuart L.; Polly, David W.; Pugely, Andrew J.; Buckwalter, Joseph A.; Albanese, Stephen A.; Bozic, Kevin J.; Snyder, Brian D.
Abstract : Abstract: Research is a foundational component of an orthopaedic residency. It fosters intellectual curiosity and pursuit of excellence, while teaching discipline and the scientific method. These are the key principles for careers in both community-based practice and academia. Currently, no consensus exists on how to best engage residents and support their research endeavors. In 2014, the American Academy of Orthopaedic Surgeons Board of Specialty Societies Research and Quality Committee convened a Clinician-Scientist Collaboration Workgroup. The workgroup's task was to identify barriers to clinical and basic science research, and to propose feasible recommendations to overcome these barriers. Herein, we have compiled the opinions of various stakeholder constituencies on how to foster scholarly pursuits during an orthopaedic residency. These opinions reflect the workgroup's conclusions that research is directly and indirectly influenced by funding, departmental support, and mentorship, and that early exposure and dedicated time to pursue scholarly activities may have a positive impact on lifelong research interests.